Influence of route of entry to a physician assistant education program on selected characteristics of practices of physician assistants. - Cavenagh JM (Journal of Physician Assistant Education (Physician Assistant Education Association), 2006)
Purpose: This study compared two groups of physician assistants (PAs), one that entered PA training through a combined Bachelor of Science/Master of Science (BS/MS) program (group 1) and another whose members entered directly after completing a bachelor's degree (group 2), on four practice characteristics: (1) primary care versus specialty practice, (2) mix of inpatients versus outpatients, (3) age categories of patients, and (4) metropolitan versus nonmetropolitan practice locations. Methods: The author used a cross-sectional telephone survey of 126 NCCPA-certified physician assistants to determine whether route of entry to training affected the selected practice characteristics. One hundred and eleven surveys were completed (88% response rate). Results: Differences were found between the two groups. Group 1 PAs (N=27) had a higher percentage practicing in primary care (as defined in the study), were more likely to see only outpatients, and reported that geriatric patients made up a higher percentage of their practices. None of this group practice in nonmetropolitan areas. Group 2 PAs (N=79) had a higher percentage practicing in specialties and seeing only inpatients, reported that nongeriatric adults comprised the highest percentage of their practices, and had a slightly higher percentage practicing in nonmetropolitan areas. The influence of route of entry on all differences between the groups was not statistically significant. Conclusion: Although not statistically significant, the differences may have implications for those who design and operate PA educational programs. However, the reasons for the differences need further study. The information gathered by this research may help in deciding how to direct limited fiscal and human resources in improving the quality of PA education.